Pendidikan dan Lingkungan Sosial, Pendidikan dan Kebudayaan, Pendidikan Sebagai Agen Perubahan - Jamilah Nur Baiti; Nadhifah Hanna Rosyidah; Tiara Nur Afidatul Isma; Sayida Nafisah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article explores the complexity of the relationship between education and society in a contemporary socio-cultural context. Through a comprehensive literature review that includes eight national and international research articles, this study analyzes the role of education in social transformation, preserving local culture, and community empowerment. The research uses a systematic review method with a narrative synthesis approach to identify patterns, themes and critical insights into the dynamics of interactions between education and the social environment. Findings show that education is a fundamental mechanism in character formation, social mobility, and cultural adaptation. This study reveals how education is not just a transfer of knowledge, but rather an agent of change that actively shapes the structure and dynamics of society. The research results emphasize the importance of an educational approach that is flexible, inclusive and responsive to cultural diversity and global challenges in the era of the industrial revolution 4.0. This article provides theoretical and practical contributions in understanding the strategic role of education in sustainable social transformation.